Diversity and Abundance of Gastropods in the Seagrass Ecosystem in the Teluk Bakau Village, Bintan Regency, Kepulauan Riau Province - Purba, Dewi Nokiana F Br; Adriman, Adriman; Fauzi, Muhammad (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2024)
The diversity and abundance of gastropods are related to the condition of seagrass. In Teluk Bakau Village, anthropogenic activities such as tourism and fish catching negatively affect the seagrass ecosystem. To understand the diversity and abundance of gastropods in that area, a study was conducted in January-March 2023. Sampling was carried out at three stations: in the area close to human inhabitants (S1), ecotourism area (S2), and in the area with no human activity (S3). In each station, there were three transect lines; in each line, there were five plots (1x1 m2). Gastropod and seagrass samplings were conducted three times. Gastropods and seagrass were collected manually from each plot and then calculated and identified. Results showed eight species of gastropods and four species of seagrass. Abundance of Gastropods was 16.13 ind/m2 in S1, 11.6 ind/m2 in S2 and 50.53 ind/m2 in S3. The most abundant gastropod in the study area was Strombus canarium, which was present in each station. The seagrass density ranged from 51-113.86 plants/m2, and the most common seagrass was Enhalus acoroides, found in each station. The results of a simple linear regression test on the relationship between seagrass density and gastropod abundance was R = 0.975 (very strong).